A Theoretical Framework of Critical Success Factors on Information Technology Project Management During Project Planning - Adzmi, Rosazlina Mohd; Hassan, Zainuddin (International Journal of Engineering and Technology, 2018)
Organizations have made significant investments in ICT projects, hoping to gain competitive advantages, growth and improvement of productivity. The success and failures of the project is one of the fields in Project Management with most frequently discussed. Project planning is an important part in the project management and has a stronger impact on project success. However, weakness in project strategy and planning lead to lack of business support, inefficient use of resources, poor estimates, poor scope control and increase risks. Previous studies have reported that well-defined project plans play an important role in the success of the project. In recent times, various factors contribute to project success namely; organizational, human, project management, complexity, quality, and technical. Hence, this study aimed to explore and identify critical success factors on project planning that lead to project success. A model is derived from findings of the literature review and tested within the Malaysian public sector through quantitative methodology. Thus, the finding of this study provide the organization with insight to drive their performance improvement in managing investments for project management field, especially through strengthening employees and organization competence as well as benefit the public’s sector.